Colonel Redl. Political motifs of the affair in Polish press releases - Stępnik, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2012)
The most famous spy scandal before the outbreak of the First World War, took place during the time of intensified diplomatic actions taken to stop the Balkan War. At night on May 24th 1913, Colonel Alfred Redl, the chief of staff for the VIII. Corps stationed in Prague – having been exposed by counterintelligence – committed suicide in Klomser Hotel in Vienna. His death was directly connected to the fact that the special commission that consisted of high ranking officers was established in the extraordinary mode. The case of Russian spy was known only to an exclusive group of ‘initiates’. Nevertheless, it was almost immediately leaked to the press and evoked scandal that stirred up public opinion in Austria-Hungary. The motifs of the scandal – described in Polish press releases of that time: in Cracow, Lvov and Warsaw – have been analyzed in the article. They were significant in the context of political struggle, led mainly between two antagonistic forces: the Austrophiles and the Russophiles. Seemingly distant from Polish matters, the spy affair turned out to be an important factor that ‘catalyzed’ political attitudes of the Poles. The aspect of Redl’s nationality became a significant element of the polemics. And the scandal undermined Austro-Hungarian morale, especially the morale of Slavic nations subject to the Empire; the more so as, at exactly the same time, a political corruption affair which Hungarian Prime Minister was involved in, happened in Budapest. The events that happened in Galicia in May and June 1913 – as connected with political and economical turning point that autonomous country reached, which was caused by Austro-Hungarian preparations for Balkan War – have been examined here as the background context. In this article, basing on a wide range of press sources, the author classifies and describes some key political motifs of the Redl affair: especially the change of ideas about the Balkan War – in accordance to common opinions expressed in Polish press – now bringing the fatal threat to Austro-Hungary. (Russia came into possession of mobilization plans). The other topics are: the decline of Austro-Hungarian prestige on the international arena, the criticism of the code applying to officer corps, assigning Redl the Jewish origin by the anti-Semitic press, attacks on the ones that supported Austro-Hungarian orientations, including those who organized a kind of ‘substitute” for Polish military forces under the auspices of the monarchy, and finally – the spy psychosis.